Ethics Review Boards for Research With Human Participants: Past, Present, and Future. (February 2021) - Peled-Raz, Maya; Tzafrir, Shay S.; Enosh, Guy; Efron, Yael; Doron, Israel (Issi)
The debate around ethics review boards (IRBs) has assumed an increasingly central place in academic practice and discourse. In this article, we summarize a unique workshop (study-group) that convened at the University of Haifa, attended by 27 academics from around the globe, representing nine countries in four continents. The participants presented data and points of view, which served as the basis for an open, interdisciplinary discussion. The group developed a set of recommendations, including working toward a transition from a review system to an advisory and validation system; focusing on respectful research approach to participants, rather than "ethical" research; building a procedure that focuses on feedback, rather than the process itself; recognizing that a unified examination need not necessarily be standardized; and constructing a feedback procedure in which researchers can respond to the review of their research.